Conflict of Az-Zaitun Islamic Boarding School - Risna Sari, Ade; Navarone Wibisono, Okki; Ryke Kalalo, Rieneke; Islami, Faisal (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2023)
The cause of the Az-Zaitun Islamic boarding school became a hot topic of discussion in the public because of several unusual things such as the association with NII, deviant teachings, and so on. Therefore, this incident caused social conflicts between the people who were pro and con against the Az-Zaitun Islamic boarding school. As a follow-up action, Menko Polhukam ordered the National Police to investigate the Az-Zaitun case. Based on this, this study aims to analyze a number of controversial cases of Az-Zaitun from a sociological point of view through the study of social theories. In addition, this study also aims to analyze this case from a normative perspective related to a number of statements by the leader of Az-Zaitun side by side with offenses and criminal elements, especially regarding blasphemy. This article is classified as qualitative research with a phenomenological approach. The results of this study show that sociologically this polemic can be constructive in order to strengthen relations between nation and state. Noramtively, Panji Gumilang's words related to the Qur'an are the essence of the prophet's kalam. Differences in prayer procedures, adhan, and so on are difficult to fulfill the offenses and elements of the blasphemy article.